Strategy Analysis Of Sikka Woven Fabric Business Development - Anresnani, Deririnda Setyo (Universitas Trunojoyo Madura, 2024)
The traditional woven fabric industry is an essential part of cultural heritage and economic development in many regions, including Sikka Regency, Indonesia. Sikka woven fabric (kain tenun Sikka) is renowned for its unique patterns, rich symbolism, and intricate craftsmanship, passed down through generations. This traditional textile industry not only serves as a representation of local identity but also plays a crucial role in supporting the livelihoods of artisans and small business owners. However, despite its cultural and economic significance, the Sikka woven fabric industry faces various challenges that hinder its growth and sustainability. The development strategy for the Sikka woven fabric craft business was designed by fgathering field data through observations, interviews, and FGD with relevant stakeholders. This study applies SWOT analysis to examine the strengths, weaknesses, opportunities, and threats influencing the development of the Sikka woven fabric business. By identifying strategic pathways, this research aims to provide recommendations to enhance competitiveness, expand market reach, and ensure the sustainability of this traditional craft in a modern economic landscape.